Champions (2016), volume 2 ebook The freelancer lifestyle. - Waid, Mark (Champions (2016), 2017)
Collects Champions (2016) #6-12. The world needs heroes, and they are the Champions! Ms. Marvel! Cyclops! Nova! Spider-Man! Viv Vision! And the Totally Awesome Hulk! They're young and idealistic, and their movement is gaining speed - but the newly minted Champions will get a harsh dose of reality when they're forced to throw down with the Freelancers! Plus: After what became of her family, Viv willingly shut down her emotions - but did her decision come at a price? And in the throes of SECRET EMPIRE, the Champions will see their world turned upside down! Broken up and scattered across the country, they still fight the good fight - but even if the world survives, the team will be divided. And by the time the conflict is over, the team's lineup may surprise you!